Policy responses to COVID-19: Why social cohesion and social protection matter in Africa - Julia Leininger; Armin von Schiller; Christoph Strupat; Daniele Malerba (German Institute of Development and Sustainability (IDOS), 2022)
This empirical analysis investigates whether and to what extent social cohesion and the coverage of social protection schemes influence governments' decisions about the stringency of COVID-19 containment policies during the first and second waves in 2020 in Africa. Our results indicate that societal and social factors influenced the stringency of containment policies. Social cohesion has a negative effect on the stringency of containment policies in response to COVID-19 over time. Social protection coverage has a positive effect on the stringency of containment policies in response to COVID-19 over time. States implemented more stringent containment policies in less cohesive societies if they already had social protection schemes in place before the pandemic. Contextual factors mediated these effects. While stringency of containment policies softened over time where levels of democracy, poverty, and inequality were higher, social protection made a mediating difference only in autocratic states and societies with higher poverty. Three contributions of the empirical analysis stand out. First, the conceptual integration of societal and social factors ("societal triangle") provides a novel basis from which to analyse policy responses during external shocks like a global pandemic. Second, to overcome the limitations of current measurements of social cohesion, we use a novel measurement to determine pre-pandemic levels of social cohesion. Third, this is the first cross-national study that addresses a world region, Africa, which has gained little attention in the study of policy responses to the COVID-19 pandemic.
Keywords: 330; social cohesion; lockdowns; social protection; containment policy; COVID-19 pandemic